PERAN KETELADANAN GURU SEBAGAI STRATEGI PEMBENTUKAN KARAKTER SOPAN SANTUN SISWA - Ahmad Makhasin Ma’arif; Ananda Suci Rahmania; Wildan Khairil Anam; Nurlaila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education through the implementation of the Pancasila Student Profile in the Merdeka Curriculum highlights the importance of courtesy as a cultural foundation in Indonesia. However, the current digital landscape and globalization have triggered the emergence of moral issues among young people, evident in the disappearance of the 5S practices (Smile, Greet, Greeting, Polite, Courteous) as well as low communication ethics. Traditional teaching methods that focus on cognition and are one-sided are considered ineffective because many students view politeness merely as an academic concept. This study aims to explore in depth the role of teachers as role models, which serves as the primary strategy in developing students’ character of politeness. By utilizing a literature review method to compile this article, it was found that the strategy of teachers serving as genuine role models includes consistency in punctuality, the use of polite language, effective emotional management, and an attitude of valuing students without discrimination.